ANTIDIABETIC EFFECT OF MALLOTUS PHILIPPINENSIS IN STREPTOZOTOCIN INDUCED DIABETIC RATS - V.NANDHINI,; DR. D. VICTOR AROKIA DOSS, (International Journal of Pharma and Bio Sciences, 2013)
In the present work the antidiabetic activity of the Mallotus philippinensis was evaluated. The hydroethanolic bark extract showed significant increase in the levels of body weight, insulin and significant decrease in blood glucose, and glycosylated haemoglobin when administered orally for 30 days to STZ induced diabetic rats at a dose of 200 and 400mg/kg body weight. Phytochemical studies also revealed the presence of phenolics in the bark extract which may be responsible to exert antidiabetic activity. Hence it can be used as a drug for diabetes mellitus.